Combination of proviral and antiviral roles of B cell-intrinsic STAT1 expression defines parameters of chronic gammaherpesvirus infection - Erika R. Johansen; Damon L. Schmalzriedt; Danilela Avila; Paul A. Sylvester; Cade R. Rahlf; Jordan M. Bobek; Daisy Sahoo; Bonnie N. Dittel; Vera L. Tarakanova (mBio)
ABSTRACT Gammaherpesviruses are species-specific, ubiquitous pathogens that establish lifelong infection in their hosts and are associated with cancers, including B cell lymphomas. Type I and II interferons (IFNs) are critical for the control of acute and chronic gammaherpesvirus infection. However, the cell type-specific role of IFN signaling during natural infection is poorly defined and is masked by the altered viral pathogenesis observed in hosts with global IFN deficiencies. STAT1 is a constitutively expressed transcription factor that is critical for the effector function of type I and II IFNs. In this study, we defined the impact of B cell-specific STAT1 expression on gammaherpesvirus infection using murine gammaherpesvirus 68 (MHV68). While the acute stage of MHV68 infection was not affected, we found opposite, anatomic site-dependent effects of B cell-intrinsic STAT1 expression during chronic infection. Consistent with the antiviral role of STAT1, B cell-specific STAT1 expression attenuated the latent viral reservoir in peritoneal B cells of chronically infected mice. In contrast, STAT1 expression in splenic B cells supported the establishment of the latent MHV68 reservoir in germinal center B cells, revealing an unexpected proviral role of B cell-intrinsic STAT1 expression during chronic gammaherpesvirus infection. These STAT1-dependent MHV68 chronic infection phenotypes were fully recapitulated in the peritoneal cavity but not the spleen of mice with B cell-specific deficiency of type I IFN receptor. In summary, our study uncovers the intriguing combination of proviral and antiviral roles of B cell-intrinsic STAT1 expression during chronic gammaherpesvirus infection.IMPORTANCEInterferons (IFNs) execute broadly antiviral roles during acute and chronic viral infections. The constitutively expressed transcription factor STAT1 is a critical downstream effector of IFN signaling. Our studies demonstrate that B cell-intrinsic STAT1 expression has opposing and anatomic site-dependent roles during chronic gammaherpesvirus infection. Specifically, B cell-intrinsic STAT1 expression restricted gammaherpesvirus latent reservoir in the peritoneal cavity, consistent with the classical antiviral role of STAT1. In contrast, decreased STAT1 expression in splenic B cells led to the attenuated establishment of gammaherpesvirus latency and decreased latent infection of germinal center B cells, highlighting a novel proviral role of B cell-intrinsic STAT1 expression during chronic infection with a B cell-tropic gammaherpesvirus. Interestingly, B cell-specific type I IFN receptor deficiency primarily recapitulated the antiviral role of B cell-intrinsic STAT1 expression, suggesting the compensatory function of B cell-intrinsic type II IFN signaling or an IFN-independent proviral role of B cell-intrinsic STAT1 expression during chronic gammaherpesvirus infection.